PEMAKNAAN KHALAYAK TERHADAP PESAN-PESAN KESETARAAN GENDER DI AKUN INSTAGRAM KONDE.CO - Aprian Teja Putra Aprian Teja Putra; Adi Nugroho (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
The rapid development of social media has created space for various media to disseminate messages of gender equality to a wider audience. One example of an alternative media platform that raises gender issues is the Instagram account of Konde.co, which frequently shares its messages through social media posts. This study aims to examine how students of Diponegoro University interpret messages of gender equality conveyed through posts on the Instagram account of Konde.co. The results show that there is a diversity of meaning positions among the informants. Most informan were positioned whitin the dominant hegemonic reading, indicating that they largely accepted the messages conveyed by the media. However, some informants also demonstrated negotiated readings on certain issues and oppositional reading on others. This diversity of interpretations is influenced by differences in background, experiences, and values held by each informant. The findings indicate that audience interpretations of gender equality messages in social media are not singular, but are shaped by various social factors and invidual experiences.